Taking the Temperature: An Intersectional Examination of Diversity Acceptance in Canadian Police Services - Bikos, Lesley (The British journal of criminology, 2023)
This exploratory study analyses data from in-depth interviews (116 from 31 police services across Canada) and an online survey (N = 727) to examine how gender and racial ideologies inform ongoing cultural and structural adherence to hegemonic whiteness and masculinity, impacting who has power (and who does not) within the institution of policing. White, cisgender, heterosexual men were the most likely to present views consistent with white supremacist patriarchy. Their ongoing cultural, structural, and material power created gatekeeping conditions that are at least part of the explanation for barriers to the recruitment and promotion of racialized women, men, and white women. Findings also reveal that a significant proportion of white women and some racialized men also upheld these ideologies, indicating cultural-level buy-in. There were disrupters who attempted to influence cultural and structural change, but barriers and resistance at leadership levels remain. Thus, this study adds to the growing body of evidence that diversity representation alone has not, and will not, transform the institution in a timely and meaningful way.